1967
DOI: 10.1021/jf60154a001
|View full text |Cite
|
Sign up to set email alerts
|

Fatty alcohol inhibition of tobacco axillary and terminal bud growth

Abstract: Fatty alcohols with chain lengths of CS, Clp, a?d C,, methyl ester. Without the proper type and amount were highly active in selectively killing or inhibitmg of surfactant, the Cg, Clo, and Cll alcohols and esters axillary and terminal bud growth of tobacco. exhibit nonselective tissue kill. With the aid of Fatty alcohols with chain lengths shorter than CS, or surfactants, the emulsions become phytotoxic only longer than CII, were less effective. On an equal to young meristematic tissue but cause little or no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1970
1970
1991
1991

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 4 publications
(6 reference statements)
0
18
0
Order By: Relevance
“…The effect of TIBA on peroxidase enzymes was confirmed by Audus and Bakhsh (2), who reported that TIBA more than doubled the rate of oxidation of IAA, and that the increase in IAA oxidase activity was due to the adaptive formation of this enzyme. brane by freezing or treating the tissues with methyl decanoate emulsions, a contact type compound that destroys cytoplasmic membranes (16,18). These results assured us that the cytoplasmic membrane did not rupture during the isolation of the cell wall fraction and that the isoperoxidase 3 is contained in the cell wall.…”
Section: Discussionmentioning
confidence: 74%
“…The effect of TIBA on peroxidase enzymes was confirmed by Audus and Bakhsh (2), who reported that TIBA more than doubled the rate of oxidation of IAA, and that the increase in IAA oxidase activity was due to the adaptive formation of this enzyme. brane by freezing or treating the tissues with methyl decanoate emulsions, a contact type compound that destroys cytoplasmic membranes (16,18). These results assured us that the cytoplasmic membrane did not rupture during the isolation of the cell wall fraction and that the isoperoxidase 3 is contained in the cell wall.…”
Section: Discussionmentioning
confidence: 74%
“…3). It is clear that the toxicity of short chain fatty acids (15,20) is due to a different mechanism than the toxicity of arachidonic acid.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we include data on the effect on nonanoic acid treatments because this fatty acid has been reported to cause necrosis of plant tissues (15,20), although it is not known to be an elicitor of phytoalexins.…”
mentioning
confidence: 99%
“…But in recent years there have been reports on the use of some chemicals that destroy actively growing meristematic tissues without affecting Received for publication May 22, 1978. 382 more mature leaf and stem tissues (2,3,4,5,6,7,8,9,12,15,16,17,18,19,20). This study deals with the effects of some chemicals used for disbudding in chrysanthemum and the methods of treatment.…”
Section: Introductionmentioning
confidence: 99%